Radiology Stereotypes, Application Barriers, and Hospital Integration: A Mixed-methods Study of Medical Student Perceptions of Radiology - Grimm, Lars J; Fish, Laura J; Carrico, Caroline Wt; Martin, Jonathan G; Nwankwo, Vesta C; Farley, Samantha; Meltzer, Carolyn C; Maxfield, Charles M (Academic radiology, 2022)
Limited exposure to radiology by medical students can perpetuate negative stereotypes and hamper recruitment efforts. The purpose of this study is to understand medical students' perceptions of radiology and how they change based on medical education and exposure. A single-institution mixed-methods study included four groups of medical students with different levels of radiology exposure. All participants completed a 16-item survey regarding demographics, opinions of radiology, and perception of radiology stereotypes. Ten focus groups were administered to probe perceptions of radiology. Focus groups were coded to identify specific themes in conjunction with the survey results. Forty-nine participants were included. Forty-two percent of participants had positive opinions of radiology. Multiple radiology stereotypes were identified, and false stereotypes were diminished with increased radiology exposure. Opinions of the impact of artificial intelligence on radiology closely aligned with positive or negative views of the field overall. Multiple barriers to applying for a radiology residency position were identified including board scores and lack of mentorship. COVID-19 did not affect perceptions of radiology. There was broad agreement that students do not enter medical school with many preconceived notions of radiology, but that subsequent exposure was generally positive. Exposure both solidified and eliminated various stereotypes. Finally, there was general agreement that radiology is integral to the health system with broad exposure on all services. Medical student perceptions of radiology are notably influenced by exposure and radiology programs should take active steps to engage in medical student education.